2022
DOI: 10.3390/ijerph191710782
|View full text |Cite
|
Sign up to set email alerts
|

The Usability of ICTs in People with Visual Disabilities: A Challenge in Spain

Abstract: The use of ICTs provides autonomy, equity, and social inclusion to people with visual disabilities. The National Organization of the Spanish Blind (ONCE) offers its 70,462 legally-blind people the necessary resources for the usability of ICTs. Still, most individuals with visual disabilities do not have a similar support system. This research aims to expose and make visible the importance and need for ICTs usage in this group. The qualitative approach has allowed the modeling of a contextualized inductive proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
1
0
2
Order By: Relevance
“…Two other categories were instantaneous social interaction and numerous contexts, in which the ubiquity and portability of the devices along with peer and instructors' interaction were relevant for the study. & Inga, 2021;Fuentes et al, 2022;Maćkowski et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Two other categories were instantaneous social interaction and numerous contexts, in which the ubiquity and portability of the devices along with peer and instructors' interaction were relevant for the study. & Inga, 2021;Fuentes et al, 2022;Maćkowski et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Jedným z najdôležitejších cieľov neziskových organizácií a vedeckých aktivít zameraných na pomoc nevidiacim ľuďom je preto snaha o ich integráciu do spoločnosti, ktorá zahŕňa aj ich pracovné uplatnenie [154,155,156,167,168]. K tomuto cieľu smeruje aj využitie nových technológií a prístupov založených hlavne na výpočtovej technike a umelej inteligencii [175].…”
Section: Asistent Správy Energetických Systémovunclassified
“…Ďalší praktický prínos súvisí so zvyšovaním samostatnosti nevidiacich pri bývaní v inteligentných budovách a ich správe. Ide o sociálne orientovaný prínos tohto výskumu [156,167,168], keďže je aj v tejto oblasti stále dominantnejší vývojový paradox DPUB -budovy sú vybavované sofistikovaným hardvérom a softvérom, ktorý ale nevidiacim neumožňuje obsluhu životne dôležitých zariadení, ako sú napr. vykurovanie, zónová regulácia, rekuperačné systémy.…”
Section: Výskum Vývoj a Výrobaunclassified
“…They conclude that many devices are not user-friendly for this aging population. Fuentes et al [35] interviewed older adults with vision impairments and reported that "accessibility is still not a priority for companies and institutions when creating and developing products".…”
Section: B Senior Citizensmentioning
confidence: 99%